Teologi Agama-agama Tipologi Tripolar; Eksklusivisme, Inklusivisme dan Kajian Pluralisme - Ahmad zamakhsari (Tsaqofah, 2020)
Tripolar typology is one of the approaches to theology of religions that was popularized by Alan Race. This typology is used as a standard in theological studies of religions, and is still widely used in the theological discourse of religions. Tripolar typology used to map various approaches theologians and theologians non-Christian on the relation of Christianity with religions. other This mapping is based on the similarities and differences in their perspective on other religions outside Christianity. The three typologies are exclusivism, inclusivism and pluralism.Komarudin Hidayat stated that there are five typologies of religious attitudes, namely "exclusivism, inclusivism, pluralism, eclecivism, and universalism". These five typologies do not mean that each is separated and disconnected from the other nor permanent, but rather it is said to be a prominent trend, considering that every religion or religious attitude always has the potential to produce the five attitudes above. Even though there are differences in theological types of religion with other religious scholars, such as Panikkar, who mentions three typologies: exclusive, inclusive, and parallelism, essentially the typological mentions contain the same meaning and meaning. Therefore, we will discuss the typologies of religion.